N6-Methyladenosine Modification of Fatty Acid Amide Hydrolase Messenger RNA in Circular RNA STAG1–Regulated Astrocyte Dysfunction and Depressive-like Behaviors - Huang, Rongrong; Zhang, Yuan; Bai, Ying; Han, Bing; Ju, Minzi; Chen, Biling; Yang, Li; Wang, Yu; Zhang, Hongxing; Zhang, Haisan; Xie, Chunming; Zhang, Zhijun; et al. (Biological psychiatry (1969), 2020)
N6-methyladenosine (m6A) is the most abundant epigenetic modification in eukaryotic messenger RNAs and is essential for multiple RNA processing events in physiological and pathological processes. However, precisely how m6A methylation is involved in major depressive disorder (MDD) is not fully understood. Circular RNA STAG1 (circSTAG1) was screened from the hippocampus of chronic unpredictable stress–treated mice using high-throughput RNA sequencing. Microinjection of circSTAG1 lentivirus into the mouse hippocampus was used to observe the role of circSTAG1 in depression. Sucrose preference, forced swim, and tail suspension tests were performed to evaluate the depressive-like behaviors of mice. Astrocyte dysfunction was examined by GFAP immunostaining and 3D reconstruction. Methylated RNA immunoprecipitation sequence analysis was used to identify downstream targets of circSTAG1/ALKBH5 (alkB homolog 5) axis. Cell Counting Kit-8 assay was performed to evaluate astrocyte viability in vitro. circSTAG1 was significantly decreased in the chronic unpredictable stress–treated mouse hippocampus and in peripheral blood of patients with MDD. Overexpression of circSTAG1 notably attenuated astrocyte dysfunction and depressive-like behaviors induced by chronic unpredictable stress. Further examination indicated that overexpressed circSTAG1 captured ALKBH5 and decreased the translocation of ALKBH5 into the nucleus, leading to increased m6A methylation of fatty acid amide hydrolase (FAAH) messenger RNA and degradation of FAAH in astrocytes with subsequent attenuation of depressive-like behaviors and astrocyte loss induced by corticosterone in vitro. Our findings dissect the functional link between circSTAG1 and m6A methylation in the context of MDD, providing evidence that circSTAG1 may be a novel therapeutic target for MDD.